Tekhnologiya osvoeniya professional'nyi geyatel'nosti trenera-prepodavatel'ya po gimnastike v aspekte mnogourevnevoi struktury vysscego obrazovaniya v Rossii - Zemskov, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to consider the problems of future specialists' on gymnastics training. The general structure of the pedagogical orientation in the professional activity of the specialists on gymnastics is represented. The qualification characteristics of specialists on gymnastic had been offered, but it needs the further study.